Exploring the role of project-based learning in higher education to promote indigenous knowledge through sculpture students’ engagement with Ghanaian Adinkra symbols - Fredrick Boakye-Yiadom; Evans Kwadwo Donkor; Ronald Osei Mensah (Discover Global Society)
Abstract This study explores the integration of Project-Based Learning (PBL) within the higher education context, focusing on sculpture learners’ projects based on Ghanaian Adinkra symbols and their engagement with Indigenous Knowledge Systems (IKS). The primary aim of this research is to examine how PBL enhances sculpture learners' understanding and appreciation of Adinkra symbols while also assessing the broader impact of PBL on their interaction with indigenous knowledge systems. Sculpture learners participating in this study were tasked with developing projects that incorporated Adinkra symbols, thereby connecting their creative practice with the rich cultural narratives embodied in these symbols. Through this process, learners were not only encouraged to produce art but also to interpret, analyse, and engage with the cultural meanings and historical significance of the Adinkra symbols. A qualitative research methodology was employed, using semi-structured interviews, participant observations, and project evaluations to gather data. Findings from the study suggest that PBL significantly enhances learners' appreciation for and understanding of indigenous knowledge systems by providing them with the tools to interpret cultural artefacts within their historical and social contexts. To collaborate with indigenous communities, art educational institutions should build partnerships with local indigenous communities, cultural experts, and artisans to co-create projects and learning experiences for learners.